A review of the Infectious Diseases Society of America (IDSA) guidelines on the diagnosis and treatment of spondylitis in adults - Karpov I.A.; Gorbich Yu.L.; Solovey N.V.; Raznitsyna O.T. (Клиническая микробиология и антимикробная химиотерапия, 2017)
Spondylitis is a common disease in general clinical practice, which can be associated with a serious risk of adverse outcomes and severe disabling effects in case of late diagnosis and inadequate management of the patient. This article provides an overview of the current clinical guidelines of the Infectious Diseases Society of America (IDSA) on the diagnosis and treatment of spondylitis in adults.